A paleodietary and subsistence strategy investigation of the Iron Age Tuoba Xianbei site by stable isotopic analysis: A preliminary study of the role of agriculture played in pastoral nomad societies in northern China. (June 2015) - Zhang, Guowen; Hu, Yaowu; Wang, Limin; Cao, Chenming; Li, Xingsheng; Wu, Xiaonong; Sun, Zudong; Chen, Fengshan; Bai, Jingsong; Lv, Peng; Song, Guoding; Wang, Changsui; et al.
Abstract: To evaluate the role that agriculture played on the diet and subsistence strategies of pastoral nomads in northern China, carbon and nitrogen stable isotopic analysis on humans and faunal bone collagen from six archeological sites dating to three periods were undertaken to investigate the paleodiet and subsistence strategies of the pastoral Tuoba Xianbei culture (ca. 100 BC–557 AD). This paper revealed the proportion shift of crops and animal proteins in the Tuoba Xianbei of the early, middle and late period. We infer that the Tuoba Xianbei were engaged in minor millet agriculture and consumed mostly animal proteins as part of a developed pastoralism in the early and middle periods. And in the late period, millet agriculture developed quickly and became one of the most important economic activities for the Tuoba Xianbei, which was likely due to the influence of the economy and culture of the Han Chinese in northern China.